Western Central Atlantic Fishery Commission - historical overview, impacts and main lessons learned - Renard, Yves (FAO RomeIT, 2010)
Documents the history and impacts of the Western Central Atlantic Fishery Commission (WECAFC) since its establishment in 1973 and provides an analysis of its influence and impact on fisheries policy, management and development in the region covered by the Commission. Offers an assessment of impacts and performance and identifies and discusses options that could provide a contribution to the formulation of decisions on the future of the Commission. Examines the structure and operations of the Commission and makes some recommendations for the future.